GRET and SIGH in the QURANIC expression Semantic study - Abbas, Dr.Khalid.K. (Thi Qar Arts Journal, 2022)
Regret, bemoan and feeling sorry are overlapping terms. Regret in the language means remorse and it has other meanings, including feeling sorry, sadness, and repentance. As for bemoan, it is the most severe case of regret for what a person has missed of things, and these concepts are achieved through linguistic methods (verbal) or through gestural movements such as ( Biting hands).